2007
DOI: 10.1016/j.cellsig.2007.08.008
|View full text |Cite
|
Sign up to set email alerts
|

c-Cbl is not required for ERK1/2-dependent degradation of BimEL

Abstract: Bim(EL) the most abundant Bim splice variant, is subject to ERK1/2-catalysed phosphorylation, which targets it for ubiquitination and proteasome-dependent destruction. In contrast, inactivation of ERK1/2, following withdrawal of survival factors, promotes stabilization of Bim(EL). It has been proposed that the RING finger protein Cbl binds to Bim(EL) and serves as its E3 ubiquitin ligase. However, this is controversial since most Cbl substrates are tyrosine phosphoproteins and yet Bim(EL) is targeted for destr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…When TRIM2 was immunodepleted from neuronal lysates we did not observe an increase in Bim ubiquitination following preconditioning ischemia. Therefore, our identification of TRIM2 as a Bim E3 ligase is consistent with the known biology of Bim ubiquitination as reported by Cook's group (11,14).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…When TRIM2 was immunodepleted from neuronal lysates we did not observe an increase in Bim ubiquitination following preconditioning ischemia. Therefore, our identification of TRIM2 as a Bim E3 ligase is consistent with the known biology of Bim ubiquitination as reported by Cook's group (11,14).…”
Section: Discussionsupporting
confidence: 76%
“…2A). Serum starvation of MEFs followed by serum stimulation has been shown to activate p42/p44 MAPK kinase and promote Bim ubiquitination (11,14). Phospho-p42/p44 MAPK levels were increased following serum stimulation of cells, and Bim protein levels were decreased accordingly ( Fig.…”
Section: Trim2-mediated Bim Degradationmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been suggested that CBL is the E3 ligase responsible for poly-ubiquitination of BIM EL ; 32 however, others fail to detect binding of BIM EL to CBL and BIM EL is turned over normally in CBLÀ/À fibroblasts arguing against this. 33 Regulation of BAD binding properties and stability. BAD is inhibited by phosphorylation at three distinct sites ( Figure 2): Ser 112 , catalysed by RSK; Ser 136 , catalysed by PKB and Ser 155 catalysed by PKA.…”
Section: Erk1/2-dependent Regulation Of Bh3-only Proteinsmentioning
confidence: 99%
“…Cells were cultured in 'complete medium', comprising [Dulbecco's modified eagle medium (DMEM) supplemented with 4.5 mg ml 21 glucose, 100 U ml 21 penicillin, 100 lg ml 21 streptomycin, 2 mM glutamine, 10% (v/v) foetal bovine serum (FBS)]. Culture of HEK293 cells expressing DRAF-1:ER* (HR1 cells) 28 or DMEKK3:ER* (HM3 cells) 30 has been described. For serum starvation, cells judged to be 50-60% confluent were washed in serum-free medium and then placed in fresh serum-free medium with 4-HT or equivalent volume of ethanol (vehicle control) for the times indicated in the figure legends.…”
Section: Cell Culturementioning
confidence: 99%